A rare case of utero-vaginal prolapse seen at third trimester: case report and review of literature - Awoniyi, Adebayo; Ugwu, Aloy Okechukwu; Garba, Sunusi Rimi; Aniugwu, Nneoma Kwemtochukwu; Egba, Augustine; Olanrewaju, Olabisi; Familusi, Oluwaseun Emmanuel; Olumakinwa, Olayemi Emmanuel; Okunade, Kehinde (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Pelvic organ prolapse (POP) is an infrequent cause of morbidity in pregnancy. We presented a case of stage three uterovaginal prolapse that was first noticed in the third trimester. Management of POP is individualized and its determined by the severity of the symptoms, stage of the prolapse, gestational age, patient’s desire and expertise of the gynaecologist. Different options of management have been proposed ranging from conservative to laparoscopy, hysterectomy in women with no desire for further child bearing. Vaginal delivery is an option; however, most obstetricians opt for elective caesarean section at term.